2019
DOI: 10.1108/pr-10-2018-0427
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic motivation, workplace learning, employer trust, self-efficacy and cross-cultural adjustment

Abstract: Purpose The purpose of this paper is to investigate the effects of extrinsic motivation, workplace learning, employer trust and self-efficacy on foreign laborers’ cross-cultural adjustment. Design/methodology/approach This paper uses structural equation modeling to analyze the data from a sample of 258 Vietnamese laborers in Taiwan. Findings The results show a significantly positive impact of extrinsic motivation, workplace learning, employer trust and self-efficacy on cross-cultural adjustment. Original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 93 publications
2
27
0
Order By: Relevance
“…The general purpose of training is to develop skills, to be faster and more effective in completing a job, to develop knowledge, so that work can be completed rationally, and to develop attitudes that foster a willingness to work together among employees and with management (leaders). From the results of this data processing, the hypothesis proposed in this research is in line with the results of previous research by Stocks and Slater (2016), Brooke et al (2017), Kerr et al (2018), Loomba and Karsten (2019), and Dang and Chou (2019) that show a positive and significant relationship between training and SE. This is according to the SE theory proposed by Bandura (1997), which states that a person must learn various skills to diagnose their strengths and weaknesses to optimize the person's potential to increase SE.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The general purpose of training is to develop skills, to be faster and more effective in completing a job, to develop knowledge, so that work can be completed rationally, and to develop attitudes that foster a willingness to work together among employees and with management (leaders). From the results of this data processing, the hypothesis proposed in this research is in line with the results of previous research by Stocks and Slater (2016), Brooke et al (2017), Kerr et al (2018), Loomba and Karsten (2019), and Dang and Chou (2019) that show a positive and significant relationship between training and SE. This is according to the SE theory proposed by Bandura (1997), which states that a person must learn various skills to diagnose their strengths and weaknesses to optimize the person's potential to increase SE.…”
Section: Resultssupporting
confidence: 89%
“…The better quality the training program provided to employees, the more SE the employees will have. Dang and Chou (2019) suggested that SE has a decisive role in employee success to understand a new culture. Training programs must encourage and emphasize employee's SE abilities.…”
Section: Effect Of Training On Self-efficacy (Se)mentioning
confidence: 99%
“…Trust generates the development of common mental models motivating employees to digital learning by systematically questioning the adopted solutions and proposing new ones (Ali et al, 2019), and therefore is the catalyst to collaborative innovation (Fawcett et al, 2012;Han and Chen, 2018). As a result, trust is a prerequisite for building a knowledge-orientated culture in an organization (Gillani et al, 2018) contributes to dispelling employees' fears related to the loss of power, prestige and usefulness in connection with the transfer of their knowledge (Jayasingam et al, 2016) and determines the involvement of employees in working for the common good, impacting job performance, goal commitment and organizational citizenship behaviors (Dang and Chou, 2019). Therefore, trust presents members with an informal code of interaction built on mutual interests and a norm of reciprocity (Tsai and Hsu, 2019).…”
Section: The Role Of Trust In the Exchange Of Professional Knowledgementioning
confidence: 99%
“…The most often cited definition, by Mayer at al. (1995), treats trust as "the willingness of a party to be valuable to the actions of another party based on the expectation that the other will perform a particular action important to the trustor, irrespective of the ability to monitor or control that other party" (Dang and Chou, 2019). The proposed in the literature on the subject terms can be reduced to a common synthetic conclusion, i.e., trust can be treated as the belief of the parties involved that each player would behave in accordance with the best interest of all partners in the cooperation relationship.…”
Section: The Role Of Trust In the Exchange Of Professional Knowledgementioning
confidence: 99%
See 1 more Smart Citation